Učitelj kot dejavnik uspešnosti v obveznem izobraževanju na Finskem - Majcen, Teja (Revija za elementarno izobraževanje, 2010)
Teacher as a success factor in compulsory education in Finland. In the following article we discuss and examine the education of class teachers in Finland as one of the factors which can lead to success in the field of primary education. The following aspects of teachers’ education are presented: decision for choosing this field of study, the changing role of a teacher and the teachers’ primary level of education (the concept and the structure of the study). These aspects are based on the changing roles, ideology for research approaches that significantly link theory and practical training, and the skills and abilities that a teacher needs in order to implement critical reflection. We have determined that the fundamental meaning in the field of educating teachers is being transformed from a phase of giving instructions and directions and how to implement educational processes into a phase where students develop skills of critical reflection, based on scientific research methods, which enable them to reflect on the development of a quality educational process. It is the creation of the so called “new teacher” who can be described as “a mentor, a researcher, a supervisor, a facilitator and a promoter for learning” and can, in that way, significantly help to increase the success of student’s mandatory education.